2010
DOI: 10.1182/blood-2010-01-259028
|View full text |Cite
|
Sign up to set email alerts
|

In vivo labeling with 2H2O reveals a human neutrophil lifespan of 5.4 days

Abstract: IntroductionNeutrophils are indispensable for host defense. 1 In addition, these cells play a detrimental role in the pathogenesis of many acute and chronic inflammatory diseases. They can cause tissue damage through aspecific activation of their repertoire of antimicrobial mechanisms. Neutrophils also inform and shape subsequent immunity 2 and can prolong inflammation by release of cytokines 3 and chemokines. 4 There is an emerging concept that neutrophils directly influence adaptive immune responses through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
569
1
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 709 publications
(598 citation statements)
references
References 18 publications
14
569
1
14
Order By: Relevance
“…1,2,10,11,[36][37][38] Although previous studies have shown that neutrophils can undergo rapid changes in gene expression upon bacterial challenge 3,4,12,13,39 or exposure to endotoxin, 3,4,10,40 it was previously unknown if and to what extent the neutrophil alters its transcriptome as it transits from the BM through the circulation and into sites of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,10,11,[36][37][38] Although previous studies have shown that neutrophils can undergo rapid changes in gene expression upon bacterial challenge 3,4,12,13,39 or exposure to endotoxin, 3,4,10,40 it was previously unknown if and to what extent the neutrophil alters its transcriptome as it transits from the BM through the circulation and into sites of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Splenic neutrophils were isolated from either control tumor-bearing mice or captopril (50 mg/kg/ d)-treated tumor-bearing mice, and exposed to CD4 C CD25 ¡ lymphocytes with anti-CD3, anti-CD28, IL-2, and TGF-b1 as previously described. 25 Since neutrophils are dying cells and the half-life of neutrophils with ex vivo manipulation is thought to be less than 24 h, 26 we examined the effect of Ly6G C cells on iTreg induction within Ly6G C cells from control tumor-bearing mice or captopril-treated tumor-bearing mice were isolated and exposed to 4T1 cells at a ratio of 10:1 for 18 h. (E) Effects of captopril on Ly6G C cells from naive mice. Blood, bone marrow, and splenic Ly6G C cells were isolated from naive mice and exposed to 500 mM captopril for 4 h, and then mean lobe counts were measured.…”
Section: Acei Polarizes Splenic Neutrophils Toward An Antitumor Phenomentioning
confidence: 99%
“…However, various stimuli, such as cytokines (G-CSF, GM-CSF) and bacterial products were shown to prolong their survival [23]. Most recent in vivo measurements estimate an extended half-life up to 5 days for circulating neutrophils [83], although there had been concerns about these data [64].…”
Section: Lifespanmentioning
confidence: 99%